URGENSI UNDANG-UNDANG KETERBUKAAN INFORMASI PUBLIK DALAM MANAJEMEN PEMBANGUNAN EKONOMI - Rosyid, Moh (Universitas Islam Negeri Sunan Kudus, 2014)
The Public Information Commission (KIP) has the role of encouraging information transparency in central and regional government agencies (pemda) and conducting education related to the era of public information disclosure to the public. Consequently, KIP members must work professionally and work optimally so that people feel their existence. This manuscript is a small part of the effort to provide an understanding to the public about the importance of the Public Information Disclosure Act for citizens, especially for economic development. The business world needs information in its entirety, starting from understanding about legislation, government policies under the law, policies of state administrators at the central and regional levels in the economic/ business field, and other aspects. If this is realized, then people's welfare will be realized through development in the field of public information. The full implementation of the KIP Law is highly dependent on the government's performance, citizens' awareness, and the role of civil society as a Nation Government Organization (NGO / NGO) that controls the performance of the government. The role of NGOs can accelerate the realization of an open government which is a strategic effort to prevent the practice of corruption, collusion and nepotism (KKN), the creation of good governance, and the realization of wise public services.